China 2049 : Economic Challenges of a Rising Global Power - Yao, Yang, 1964-; Huang, Yiping, 1964-; Dollar, David (Book collections on Project MUSE., 2020)
"It's clear that China is the world's next economic superpower. But what isn't so clear is how China will get there by the middle of this century. It now faces tremendous challenges such as fostering innovation, dealing with an ageing population, and coping with a less accommodative global environment. In this book, economists from China's leading university and the Brookings Institution offer in depth analyses of these challenges. The book provides unique insights into independent analyses and policy recommendations by a group of top Chinese and American scholars. Whether China succeeds or fails in economic reform will have a large impact, not just on China's development, but also on stability and prosperity for the whole world"--